164 EFFECTIVENESS OF ONE-TIME ENDOSCOPIC SCREENING PROGRAM IN PREVENTION OF ESOPHAGEAL CANCER IN CHINA: A MULTI-CENTER POPULATION-BASED COHORT STUDY. (14th September 2020) - Chen, R; Liu, Y; Song, G; Li, B; Zhao, D; Hua, Z; Wang, X; Li, J; Hao, C; Zhang, L; Liu, S; Wang, J; et al.
Abstract: : Esophageal cancer is one of the most common cancers worldwide and half of all new cases occurred in China. Population-based endoscopic screening has been carried out in some high-risk areas in China since 2005, but previous evidence was based predominately on small-sample, single-center studies. We undertook a population-based, multi-center cohort study to estimate the effectiveness of endoscopic screening program in reducing the incidence and mortality of esophageal in high risks areas in China. Methods: This study was conducted in six areas in China from 2005 to 2015. All permanent residents aged 40–69 yeas were identified as target subjects. We defined those who were invited and undertook endoscopic screening as the screened group, and those who refused screening as the non-screened group. The target subjects who were not invited to screening was assigned to the control group. The effectiveness of endoscopic screening and screening program were evaluated by comparing the reductions in the incidence and mortality from esophageal cancer in those screened or those invited to screening with reductions in the control group, respectively. Results: Our cohort analysis included 637 500 people: 299 483 in the control group and 338 017 in the invited to screening group, 113 340 (33.53%) of whom were screened eventually. Compared with subjects in the control group, esophageal cancer incidence and mortality were reduced by 26% (relative risk(RR) 0.74, 95% confidence interval(CI), 0.69–0.79) and 60% (0.40, 0.36–0.45) respectively in those screened, and they were reduced by 15% (0.85, 0.82–0.89) and 33% (0.67, 0.63–0.71) respectively in those invited to screening. Conclusion: Among individuals aged 40–69 years in high risk areas of esophageal cancer, one-time endoscopic screening program was associated with a significant decrease in esophageal cancer incidence and mortality.